The efficacy of mindfulness meditation apps in enhancing users’ well-being and mental health related outcomes: a meta-analysis of randomized controlled trials - Gál, Éva; Ștefan, Simona; Cristea, Ioana A. (Journal of affective disorders, 2021)
•App- delivered mindfulness meditation interventions have small to medium effects on perceived stress, symptoms of depression and anxiety•No significant effects were found for general well-being and distress at post-test•The intervention's effect was maintained at follow-up for perceived stress, symptoms of anxiety and quality of life•Comparable effects were found in comparison with attention control conditions Mindfulness applications are popular tools for improving well-being, but their effectiveness is unclear. We conducted a meta-analysis of randomized controlled trials (RCTs) that employed a mindfulness meditation app as the main intervention to improve users’ well-being and mental-health related outcomes. A systematic search was conducted in PsycINFO, PubMed, Web of Science, ProQuest Dissertations and Theses Global, the Cochrane Library, Open Grey and ResearchGate through June, 2020. Effects were calculated as standardized mean difference (Hedges’ g) between app-delivered mindfulness interventions and control conditions at post-test and pooled with a random-effects model. From 2637 records, we selected 34 trials (N = 7566). Significant effect sizes were found at post-test for perceived stress (n = 15; g = 0.46, 95% CI [0.24, .68], I2= 68%), anxiety (n = 15; g = 0.28, 95% CI [0.16, .40], I2= 35%), depression (n = 15; g = 0.33, 95% CI [0.24, .43], I2= 0%), and psychological well-being (n = 5; g = 0.29, 95% CI [0.14, .45], I2= 0%). No significant effects were found for distress at post-test (n = 6; g = 0.10, 95% CI [-0.02, .22], I2= 11%) and general well-being (n = 5; g = 0.14, 95% CI [-0.02, 0.29], I2 = 14%). Mindfulness apps seem promising in improving well-being and mental-health, though results should be interpreted carefully due to the small number of included studies, overall uncertain risk of bias and heterogeneity.